The Effect of Verb Story Game towards Students’ Motivation in Learning Grammar - Deni Suryani (Universitas Pendidikan Mandalika, 2018)
This research was aimed to find out the effect of Verb Story game towards students’ motivation in learning grammar. The research was experimental research and the design that was used was post-test only design. The population of the study was the second grade students of MTs Aunul Ibad NW Beroro course which consisted of four classes. Two classes were chosen as the samples, those were MTs Aunul Ibad NW Beroro A Class as experimental group consisted of twenty four students and C Class as control group consisted twenty four students. They were chosen by using Simple Random Sampling technique. Experimental group was treated by Verb Story game and control group was treated by Verb Search game. The instrument that was used objective test and questionnaire in forms of multiple choices and matching word. Then, the scores were analyzed by using statistical analysis. It showed the mean score of experimental group was 73,16 while the mean score control group was 55,12 and the value of t (t test) = 3,537 was higher than the value of (t table) = 2, 013 at the significance level of 5% and the number of degree freedom (46). Therefore, according to the result of the analysis, it can be concluded that it can be concluded that the use of verb story game is effective in learning grammar at second grade students of MTs Aunul Ibad NW Beroro and the result correlation between students’ motivation and grammar, it shows r-test (0,993) > r-table (0,404). Based on the result of the study, it can be conclude there is correlation between students’ motivation and grammar is accepted. In other word, alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected.